Pengaruh Karakteristik Individu Dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja Dengan Budaya Organisasi Sebagai Variabel Intervening Pada PT. Perta Arun Gas - Budi Mulia; Marbawi Marbawi; Sapna Biby (J-MIND (Jurnal Manajemen Indonesia), 2021)
Abstract: This study aims to determine how much influence the individual characterstic and job characteristic through organization culture and its impact on job satisfaction of PT. Perta Arun Gas Lhokseumawe City. The data used is the data by distributing questionnaires to 168 employee PT. Perta Arun Gas Lhokseumawe City. To analyze the data, the statistical analysis used structure equation modeling (SEM) and processed with the help of the application Amos. The variables measured include individual characterstic and job characteristic effect toward organization culture of The PT. Perta Arun Gas Lhokseumawe City. Based on the analysis of statistical test is individual characterstic and job characteristic and organization culture affect on the job satisfaction of PT. Perta Arun Gas Lhokseumawe City. The result organization culture variable effect of full mediated on individual characterstic and job characteristic toward to job satisfaction of PT. Perta Arun Gas Lhokseumawe City. Keywords : Individual Characterstic, Job  Characteristic,  Organization  Culture and Job Satisfaction.